Telomere- and Telomerase-Associated Proteins and Their Functions in the Plant Cell - Procházková Schrumpfová, Petra; Schořová, Šárka; Fajkus, Jiří (Frontiers in Plant Science, 2016)
Telomeres, as physical ends of linear chromosomes, are targets of a number of specific proteins, including primarily telomerase reverse transcriptase (TERT). Access of proteins to the telomere may be affected by a number of diverse factors, e.g. protein interaction partners, local DNA or chromatin structures, subcellular localization/trafficking or simply protein modification. Knowledge of composition of the functional nucleoprotein complex of plant telomeres is only fragmentary. Moreover, the plant Telomeric Repeat Binding (TRB) - proteins that were characterized recently appear to also be involved in non-telomeric processes, e.g. ribosome biogenesis. This interesting finding was not totally unexpected since non-telomeric functions of yeast or animal telomeric proteins, as well as of telomerase subunits, have been reported for almost a decade. Here we summarize known facts about the architecture of plant telomeres and compare them with the well described composition of telomeres in other organisms.